Diagnostic Discipleship Mark 10:17-31 Proper 23 [28] - Adams, Marilyn McCord (The expository times, 2006)
The article focuses on the meaning of discipleship based on interpretation of the biblical text Mark 10:17. A rich young man who has been following the Ten Commandments approached Jesus to know how can he attain eternal life. The author says that the rich man had done this because he believed that he must move on from a higher level of discipleship.